Influence of Anticipation on Neuromuscular Control During a Single‐Leg Diagonal Drop Jump Landing Task In Female Football Players. A Cross‐Sectional Study. - Miralles‐Iborra, A.; Dos'Santos, T.; Elvira, J. L. L.; Esteban‐López, M.; Del Coso, J.; Moreno‐Pérez, V. (European Journal of Sport Science, 2026)
The impact of anticipation during a football‐specific action on neuromuscular control in female football players is underexplored. To investigate the influence of anticipation on trunk and lower limb kinematics during a single‐leg diagonal drop jump test in female football players. Twenty‐eight amateur football players performed two drop jumps per leg in two directions: ipsilateral and contralateral (same or opposite side of the landing leg, respectively) under anticipated and unanticipated conditions. In the anticipated condition, the jump direction was known before landing, whereas in the unanticipated condition, it was indicated by a visual light stimulus presented before ground contact. The sagittal and frontal planes of the first landing were recorded for 2D video analysis. Female football players exhibited longer ground contact time (p < 0.001; ES = 1.649–1.798) during unanticipated jumps. Unanticipated trials were performed with greater trunk, hip and knee flexion, and this was already evident at initial contact (ηp2 ≈ 0.16–0.18) and became very large by final contact (ηp2 ≈ 0.60–0.69). Trunk lateral flexion and hip abduction decreased during unanticipated ipsilateral jumps (p ≤ 0.005; ES = 0.83–1.76) but increased during unanticipated contralateral jumps (p ≤ 0.002; ES = −0.67–[−1.74]). Additionally, the medial knee position increased in unanticipated ipsilateral jumps (p < 0.001; ES = −1.89) but decreased in unanticipated contralateral jumps (p = 0.005; ES = 0.62). Unanticipated landings increase ground contact time, promote flexed sagittal strategies and affect frontal kinematics differently influenced by the subsequent jump direction in female football players. Highlights: Female footballers show distinct neuromuscular profiles in anticipated versus unanticipated jumps.Unanticipated landings increase ground contact time and promote flexed sagittal strategies.Unanticipated subsequent jump direction affects kinematics on the frontal plane.